Dampak Kerja Shift dan Tingkat Stres terhadap Kadar Gen Brain-Derived Neurotrophic Factor (BDNF) pada Perawat Selama Pandemi Covid-19 - Atthariq; Maria Eka Putri; Muhammad Fachri; Risky Akaputra; Dede Renovaldi (PENGURUS BESAR IKATAN DOKTER INDONESIA (PB IDI), 2025)
Introduction: The project aims to investigate how the Covid-19 epidemic influenced nurses’ stress levels, shift work, and BDNF mRNA expression. Hospitalized patient numbers in Indonesia were rising sharply during the outbreak. This illness has a major impact on nurses’ levels of weariness and stress, which follow each other. High-stress workers have lower serum levels of brain-derived neurotrophic factor (BDNF). Workload, job conflicts, and sleep difficulties are some of the causes that lead to this stress.Methods: The study was conducted at the Cempaka Putih Islamic Hospital in Central Jakarta, Indonesia, from July to September 2020. The study used an analytical observational approach and a cross-sectional design. The number of nurses who participated in this study was 89 people who were selected using This study included 89 nurses who were recruited using a purposive selection technique based on predetermined inclusion and exclusion criteria. Anthropometric measures and intravenous blood collection were used to gather data for real-time PCR analysis of the BDNF gene mRNA expression.Result: The mean BDNF mRNA expression level was 8.93 ng/mL. Nurses reported work-related stress, with a significant correlation (p less than 0.05) between BDNF mRNA expression, work shift, and stress levels. According to the findings, those with low, moderate, and high stress levels had mean BDNF levels of 11.69, 8.65, and 7.36, respectively. Statistical testing revealed a significant difference (p less than 0.001) in the mean mRNA expression of the BDNF gene across subjects with low, moderate, and high stress levels.Conclusion: During the Covid-19 pandemic, a statistical correlation was found between nurse stress levels, work shifts and low BDNF levels.